2021
DOI: 10.3390/genes12101519
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Models for Charcot–Marie–Tooth Neuropathy Related to Aminoacyl-tRNA Synthetases

Abstract: Aminoacyl-tRNA synthetases (aaRS) represent the largest cluster of proteins implicated in Charcot–Marie–Tooth neuropathy (CMT), the most common neuromuscular disorder. Dominant mutations in six aaRS cause different axonal CMT subtypes with common clinical characteristics, including progressive distal muscle weakness and wasting, impaired sensory modalities, gait problems and skeletal deformities. These clinical manifestations are caused by “dying back” axonal degeneration of the longest peripheral sensory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Notably, it has been proven that most CMT mutations of AARSs are related to the weakened dimer ( 61 , 64 ). Dimer disassociation likely plays an important role in both the loss-of-function and gain-of-function mechanisms of the development of AARS-associated CMT diseases ( 61 , 65 ). In this study, gel filtration assays revealed that even wild-type Ec TrpRS has the potential to dissociate from dimer to monomer, especially in the apo state.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has been proven that most CMT mutations of AARSs are related to the weakened dimer ( 61 , 64 ). Dimer disassociation likely plays an important role in both the loss-of-function and gain-of-function mechanisms of the development of AARS-associated CMT diseases ( 61 , 65 ). In this study, gel filtration assays revealed that even wild-type Ec TrpRS has the potential to dissociate from dimer to monomer, especially in the apo state.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction triggers a transcriptional response that subsequently alters neurodevelopment, dendrite morphogenesis, and glucose metabolism ( 12 ). It is noteworthy that the manifestations of ARS-associated CMT are primarily attributed to length-dependent axonal degeneration rather than demyelination ( 13 ). In the case of YARS1-associated CMT, upper extremity weakness and atrophy, along with hyperreflexia, have been reported ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…This implied that point mutations, such as E71G and L129P, cause the variations resulting in a loss of function. 7,110 Few studies have reported the lowering of aminoacylation activity of GlyRS by the nine CMT-causing mutations, which are G526R, G240R, G598A, P244L, A57V, D146N, I280F, H418R, S211F, and the gars1Δ yeast strain is not saved by these variants. 104,111 The second AaRS linked to CMT is TyrRS; it was discovered to have a mutant residue (G41R) in the ATP recognition area, which might affect the binding of ATP with TyrRS, whereas charge reversal was observed in the mutant (E196K), which may alter the structural integrity of TyrRS.…”
Section: Aarss In Neuronal Diseasesmentioning
confidence: 99%
“…In the Drosophila model of the GlyRS‐induced CMT2D, neuronal abnormalities, such as axonal and dendritic defects in mushroom body ˠ neurons, along with severe dendritic defects in olfactory projections, were detected. This implied that point mutations, such as E71G and L129P, cause the variations resulting in a loss of function 7,110 . Few studies have reported the lowering of aminoacylation activity of GlyRS by the nine CMT‐causing mutations, which are G526R, G240R, G598A, P244L, A57V, D146N, I280F, H418R, S211F, and the gars1Δ yeast strain is not saved by these variants 104,111 …”
Section: Role Of Aarss In Diseasesmentioning
confidence: 99%